Role and Duty of an Archivist in the Chain of Social Responsibility for the Protection of Confidential Information and Personal Data (Atlanti, 2016)
This paper deals with the role and responsibility of archivists in the modern era in which, primarily due to the application of new technologies, all data and pieces of information from current and archival records, including those personal and confidential ones, become potentially “visible”, i.e. available to the general public in any given moment. Dual responsibility of archivists is adduced in personal and confidential data protection: archivist as a creator / holder of current and archival records containing this kind of data, and as a custodian and processor of archival material of other creators and holders. Through various stages in the course of the performance of their professional archival work a degree of responsibility of archivists has been analysed in the protection of personal / confidential data. The need, as well as the importance of the regular alignment of the national archival regulations with other legal acts and recommendations concerning the above-mentioned areas have been pointed out. Also, the necessity of making detailed elaborated professional instructions-guidelines for archivists as to how, in the process of their professional work, to manage personal data and classified information contained in the current and archival records has been underlined. Some positive and negative practices in Montenegro are presented, with special reference to the specificities of the small states and their ability to fully implement international community directives and recommendations in the field of the protection of privacy and confidentiality.
Keywords: access; new technologies; data protection; personal data; confidential data; archival regulations